Unveiling the Nexus: Digital Forensics and Gender in Law – A Rich Dataset for Global Scholars - Artanti Tertia Mukti; Sri Budi Purwaningsih; Anita Rohma Fidayanti (Proceedings of The ICECRS, 2023)
In this data article, we conducted a comprehensive search on the Lens.org website using the keywords "Digital forensic" and "female," resulting in the identification of 6,280 documents. Subsequently, we refined our search by filtering for journal articles, which yielded 5,123 relevant documents. Further narrowing our focus, we selected a date range spanning from 2012 to 2022, resulting in 4,115 documents. Finally, by filtering for the subject matter "Law," we obtained a subset of 301 documents. The data gathered here serves as a valuable resource for researchers and scholars seeking to explore the intersection of digital forensics and gender-related aspects within the legal domain. The significant volume of documents underscores the growing importance of this field, offering a rich foundation for future studies and experiments in understanding the complexities of digital forensics in relation to gender and legal contexts.Highlights : Extensive dataset: A vast collection of 6,280 documents. Research focus: Intersection of digital forensics, gender, and law. Valuable resource: Facilitating in-depth studies and experiments. Keywords: Digital forensics, Gender, Law, Dataset, Research Impact